SISTEM INFORMASI GEOGRAFIS PENENTUAN RUTE TERPENDEK LOKASI VILLA MENGGUNAKAN ALGORITMA FLOYD WARSHALL - Hendro Wijayanto; Didik Nugroho; Beni Aryo Santoso (STMIK Sinar Nusantara, 2020)
District Tawangmangu has many types of villa that can be able to the local people and the community itself. Information about where the villa is needed by tourists also the general public is the route information to the villa in district Tawangmangu. The aim of the research is to apply Floyd Warshall algorithm in finding the shortest route for villa in Tawangmangu District which has 150 and about 30 which will be displayed in the Web interface with the help of Google Maps API. The closest villa location to the Grojokan sewu tourist is the villa Indra Sari with a yield of 245 meters. As well as comparisons with Google Maps got results 80% of the 30 different test paths and due diligence with respondents showed a feasibility rate of 88,75% indicating that the application made is well-deserved by the user, Floyd Warshall algorithm is applied because the principle held by the algorithm Floyd Warshall is the principle of optimality. The result is an application that can show the shortest route, along with from the starting location to the destination location of the villa.